Model Literasi Al-Qur’an Berbasis Audio Visual pada Pembelajaran Al-Qur’an di Madrasah Ibtidaiyah Pergis Bonde Kec. Campalagian Kab. Polewali Mandar - Nusriani Nusriani; Nurhayati Nurhayati; Marhani Marhani; Usman Usman; Muh. Akib (Departement of Mathematics Education, 2023)
Efforts to familiarize students with reading and writing the Koran in the learning process sometimes do not always go well. This study aims to describe: 1) the Qur'anic literacy model; 2) use of audio-visual media; 3) implementing learning to read and write the Koran through the audio-visual-based Al-Qur'an literacy model at Madrasah Ibtidaiyah Pergis Bonde. This type of research is a qualitative research. The object of this research is Madrasah Ibtidaiyah Pergis. Data collection used interview, observation and documentation techniques, then analyzed using reduction analysis, display and verification analysis stages and drawing conclusions. The results of this study indicate that: 1). Al-Qur'an literacy in Madrasah Ibtidaiyah is carried out every day at the beginning of learning. This activity lasts approximately 30 minutes for each subject in the first hour. The Al-Qur'an literacy model is carried out using the habituation method with the hope that the Al-Qur'an reading and writing habituation method will have a positive impact on students, especially the inculcation of Al-Qur'an values ​​that can be practiced in everyday life. day. 2). Audio-visual media in learning is taken using a projector (LCD). 3). Audio-visual-based Al-Qur'an literacy is carried out by presenting verses of the Qur'an in front of students. The verses are displayed using a projector and assisted by loudspeakers so that students can see and hear the verses properly. After that is done, students are then given the opportunity to read the verses based on the teacher's orders, and then each writes down what he has read.